Study the Rate Constant of Photostabilization of PVC in Presence of Schiff’s Bases of Sulphamethoxazole - Hussain, Zainab; Yousif, Emad; Altaie, Ali; Zageer, Dheaa (Al-Nahrain Journal of Science, 2018)
The photostabilization of poly (vinyl chloride) (PVC) films by Sulphamethoxazole Schiff's bases compounds was investigated. The PVC films containing concentration of compounds 0.5% by weight were produced by casting method from tetrahydrofuran (THF) solvent. The photostabilization activities of these compounds were determined by calculating the photodegradation rate constant for photostabilizer (kd). The stabilizing efficiency of sulphamethoxazole–Schiff’s base derivatives is attributed to the replacement of the labile chlorine atoms on the PVC chains by a relatively more stable moiety of the organic stabilizer.